Selective Formation of Trimethylene Carbonate (TMC): Atmospheric Pressure Carbon Dioxide Utilization. Issue 3 (10th December 2014) - Buckley, Benjamin R.; Patel, Anish P.; Wijayantha, K. G. Upul
Abstract: Carbon dioxide utilisation (CDU) is currently gaining increased interest due to the abundance of CO2 and its possible application as a C1 building block. We herein report the first example of atmospheric pressure carbon dioxide incorporation into oxetane to selectively form trimethylene carbonate (TMC), which is a significant challenge as TMC is thermodynamically less favoured than its corresponding co‐polymer. Abstract : The first atmospheric pressure carbon dioxide incorporation into oxetane to selectively form trimethylene carbonate (TMC) is reported. This is a significant challenge since TMC is thermodynamically less favoured than its corresponding co‐polymer. This system is capable of converting a 3, 3‐substituted oxetane to the corresponding cyclic carbonate in good yield.